The impact of school violence on teaching and learning in secondary schools in the Capricorn South District of Limpopo Province - Magdeline, Teffo Maphuti; Jacob, Segalo Letlhoyo; Tsakane, Ngobeni Elias (World Journal of Vocational Education and Training, 2024)
Violence in schools has become a concern to the learners, teachers, parents and other stakeholders in Mphahlele Circuit at Capricorn South District of Limpopo Province. The learners fight amongst themselves and against their teachers. In some instances they stab one another. The teachers and the learners are not safe at their schools, whereas schools are supposed to be safe havens for teaching and learning. Given all these challenges in Mphahlele schools, the proposed study sought to investigate if really there is violence in the schools and also to explore the nature thereof. Also, the study sought to investigate the contributory factors and the preventative measures to violence. The study followed a mixed-method research strategy and used surveys and interviews. The researcher used purposive sampling to select participants for the research. Twelve (12) participants were selected for qualitative study which used interviews. The questionnaires were used to collect data from fifty (50) participants in quantitative research. Data was analyzed using the codes and themes. The study revealed that the learners bully each other, bring weapons to school, and have gangs. The learners and teachers miss contact time during disciplinary hearings and that impacts negatively on the performance of the learners and the completion of the syllabus. The social problems, economic and family instabilities, drugs and alcohol abuse seemed to be the contributing factors. The study recommended that parents, churches, government and non-governmental organizations and the schools should collaborate to minimize violence, as one strategy in isolation cannot prevent school violence.